Assimilation and other determinants of school attainment in Germany: Do immigrant children perform as well as Germans? - John P. Haisken-DeNew; Felix Büchel; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
The German secondary school stream-system has three levels: minimum (Hauptschule), general (Realschule), and university-entry (Gymnasium). Using the German Socio-Economic Panel (GSOEP), we examine determinants of school attainment of German and foreign pupils in West Germany 1984-1993 using an ordinal probit model. Unlike standard specifications, we augment with controls for parental ability and income preference. Further, detailed regional level information is introduced to control for schooling supply conditions. Foreign childen have a much higher probability of only attaining the lowest level of education. However, assimilation reduces this effect. Ability or income preference, is shown very clearly to increase the probability of a child's Gymansium attainment1.
Keywords: J15; J24; I21; C25; 330; Educational Attainment; Foreigner Assimilation; Ability; Income Preference; Ordinal Probit; Marginal Effects; Pseudo R2